Pengaruh DPK, BOPO, CAR dan LDR Terhadap Kinerja Keuangan (ROA) - Riris Ratna Fatnanda, 09.05.52.0117; Aini, Nur (Students Journal of Accounting and Banking, 2013)
Banks play an important role for economic development as a Financial Intermediary or intermediary party excess funds to the needy. Assessment of financial performance is one of the important factors for banks to see how the performance of the bank in doing what is good or not. Study was to analyze jointly DPK, ROA, CAR, and LDR on financial performance (ROA).The sample was selected using purposive sampling method. With a total sample of 78 data. Future observations by the author in 2009 to 2011. Financial ratio analysis is also used to determine the level of performance and health of a bank using a ratio calculation DPK,BOPO,CAR and LDR. Data analysis method used is the classic assumption test, normality test using skwenes kurtosis test and regression test using SPSS tool.The results showed that the deposits have a positive and significant impact on financial performance (ROA) ROA negative and significant effect on the financial performance (ROA), while CAR and LDR no effect on financial performance (ROA).Keywords: Dana Pihak Ketiga, Biaya Operasional terhadap Pendapatan Operasional, Capital Adequacy Ratio, Loan to Deposit Ratio dan Return On Asset